Stroke, Post Stroke, Drinking Pills Āngōng Niúhuangwan? - Alfredo Aldo Eka Putra Tjundawan; Onny Priskila; Mellisa; Ferdinand; Suryawan Ang; Agus Sugiono (Science Midwifery, 2022)
Introduction: Global Burden of Disease shows that globally, the risk of stroke has increased to 1 in 4 people. This underlies the World Stroke Organization to hold a stroke awareness campaign. Stroke is the second leading cause of death and the third leading cause of disability worldwide. According to the World Health Organization, stroke is a condition in which clinical signs develop rapidly in the form of focal and global neurologic deficits, which can be severe and last for 24 hours or more and cause death without any other apparent causes other than vascular. In addition, stroke is also a contributing factor to dementia and depression. Purpose: This study aims to reveal the importance of taking āngōng niúhuángwán pills during and after a stroke. Method: Conducted a literature review by searching through electronic databases Garuda, Pubmed, and Google Scholar and obtained three relevant research articles from 2011-2021 based on inclusion and exclusion criteria. Result: After being given āngōng niúhuángwán pills, it was found that there was an improvement in the quality of life in post-stroke patients. Conclusion: Taking āngōng niúhuángwán pills is effective in improving the quality of life in post-stroke patients.